Cutis laxa for diagnosis of γ1‐heavy‐chain deposition disease: Report of four cases. Issue 10 (23rd July 2018) - Chavarot, Nathalie; Battistella, Maxime; Vignon, Marguerite; Baron, Marine; Girerd, Sophie; Jachiet, Marie; Asli, Bouchra; Galicier, Lionel; Malphettes, Marion
Abstract: Heavy‐chain deposition disease (HCDD) is characterized by tissue deposits of a truncated monoclonal immunoglobulin heavy‐chain (HC) on basement membranes. Diagnosis is usually made on kidney biopsy, showing nodular glomerulosclerosis with HC deposits which can be missed, resulting in delay in diagnosis. We report four γ1‐HCDD patients presenting with cutis laxa, hypocomplementemia and hypoalbuminemia. In two patients, unsuspected HCDD was revealed by cutis laxa and diagnosis was made on skin biopsy. In all patients, serum albumin and complement represented surrogate markers for disease monitoring. In γ‐HCDD, extrarenal manifestations such as cutis laxa may precede renal injury and are precious tools for an early diagnosis, which is crucial to avoid progression of irreversible renal and elastic tissue damage.